Pengukuran Kinerja Dengan Rasio Keuangan dan Economic Value Added (EVA) Pada PT Bank Muamalat Indonesia Tbk - Arsad S (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
The purpose of this research is to measure the performance of PT Bank Muamalat Indonesia Tbk using financial ratio and EVA. Financial ratio measured by profitability ratio, which consists of return on assets (ROA), return on equity (ROE), operating expenses, and net profit margin (NPM), while the value of EVA obtained from NOPAT minus capital charge. The data that used in this research is annual report of bank muamalat from 2008 until 2012. The result of this research is the measurement of performance of bank using financial ratio shows improvement from year to year, although in 2009 the performance of bank had decreased, while the measurement of performance using EVA shows that the best performance is achieved by bank occurred in 2009. The comparison of measuring performance between financial ratio and EVA is the performance of company if measured by financial ratio shows improvement, except in 2009, but if measured by EVA, the performance of company in 2009 is the best performance.